A modified asphalt compatibility quantitative evaluation method based on fluorescence image analysis and a modified asphalt modifier content optimization method

CN122631611BActive Publication Date: 2026-11-03CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611122174.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-11-03
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

Existing methods for evaluating the compatibility of modified asphalt are influenced by many factors, are highly subjective, have poor repeatability, and cannot guide actual formulation production.

Method used

A fluorescence image analysis-based method was adopted. By setting a first threshold and a second threshold for fluorescence grayscale values, the modified asphalt image was segmented into a strong fluorescence phase, a weak fluorescence phase, and a non-fluorescent phase. The ratio of the area of ​​the weak fluorescence phase to the total fluorescence area was calculated as the compatibility index. By constructing a curve showing the relationship between the modifier dosage and the compatibility index, the optimal dosage of the modifier was determined.

Benefits of technology

It enables quantitative evaluation of the compatibility of modified asphalt, reduces human error, provides a scientific basis for formulation design, and improves the accuracy and controllability of modified asphalt material design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122631611B_ABST
    Figure CN122631611B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of road engineering, and particularly relates to a modified asphalt compatibility quantitative evaluation method based on fluorescence image analysis and a modified asphalt modifier content optimization method. The fluorescence image is segmented into a strong fluorescence phase, a weak fluorescence phase and a non-fluorescence phase according to a fluorescence gray threshold. The compatibility index is defined as the ratio of the weak fluorescence phase area to the total fluorescence area, and a gray value threshold rule is set to ensure the objectivity and repeatability of the segmentation result. Based on the above method, modified asphalt samples with different modifier contents are prepared, the compatibility index under each content is calculated, and the critical inflection point is determined as the judgment basis for the best addition amount of the modifier according to the content-compatibility curve. The method realizes the accurate quantitative evaluation of the compatibility of the modified asphalt, can quickly guide the formula optimization of the composite modification system, and has important significance for improving the design level of the modified asphalt and the durability of the road engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of road engineering technology, and in particular to a quantitative evaluation method for the compatibility of modified asphalt using fluorescence image analysis and a method for optimizing the dosage of modifiers in modified asphalt. Background Technology

[0002] The microstructure of polymer-modified asphalt (such as styrene-butadiene-styrene block copolymer modified asphalt) is closely related to its macroscopic road performance. The compatibility between the modifier and the asphalt matrix directly affects storage stability, workability, and road durability. Therefore, establishing a method to accurately evaluate compatibility is crucial for the optimization and quality control of modified asphalt formulations.

[0003] Currently, compatibility evaluation methods are mainly divided into two categories. The first category is based on macroscopic performance or storage stability tests, such as softening point difference, segregation test, viscosity, and rheological parameters. Although these methods can reflect the final effect, they are affected by multiple factors such as temperature, test conditions, and aging, making it difficult to attribute them solely to compatibility issues and unable to reveal the microscopic improvement mechanism. The second category uses fluorescence microscopy to directly observe the polymer phase distribution, but existing image analysis is mostly based on empirical descriptions (such as "whether the dispersion is uniform" or "whether it forms a network"), which are highly subjective and have poor repeatability. A few evaluation methods attempt to quantify fluorescence area, but they are often simply binarized into "fluorescent / non-fluorescent," failing to distinguish between the modifier-enriched phase and the modifier-asphalt transition mixing zone, resulting in a mismatch between the characterization results and the actual phase structure. In addition, fluorescence imaging is easily affected by factors such as sample thickness, exposure parameters, and uneven illumination, making it difficult to make lateral comparisons between different batches of samples, thus limiting its application in engineering standardization and batch testing. Furthermore, existing compatibility evaluation methods only summarize the performance of prepared polymer-modified asphalts and do not extend to providing preparation guidance on how to optimize the performance of polymer-modified asphalts.

[0004] Therefore, there is a need for a method that can assign clear physical meaning to the microscopic phase region, eliminate imaging condition interference, and quantitatively evaluate the compatibility of modifiers and asphalt, so as to provide an objective and reliable basis for the formulation design, mechanism analysis and quality control of modified asphalt. Summary of the Invention

[0005] This invention provides a quantitative evaluation method for the compatibility of modified asphalt based on fluorescence image analysis and a method for optimizing the dosage of modifiers in modified asphalt. The purpose is to solve the problems of existing compatibility evaluation methods, such as many influencing factors, strong subjectivity, poor repeatability, and inability to guide actual formulation production.

[0006] To achieve the above objectives, this invention provides a method for quantitative evaluation of the compatibility of modified asphalt based on fluorescence image analysis, comprising the following steps: (1) Obtain fluorescence images of modified bitumen; (2) The fluorescence image of the modified asphalt is divided into a strong fluorescence phase, a weak fluorescence phase and a non-fluorescent phase according to the fluorescence gray value, wherein the strong fluorescence phase corresponds to the modifier-enriched phase and its area is denoted as A, and the weak fluorescence phase corresponds to the modifier-asphalt compatible transition phase and its area is denoted as B. (3) Calculate the ratio of the area of ​​the weak fluorescent phase to the total fluorescent area, and use this ratio as the compatibility index of the modified asphalt; the total fluorescent area is the sum of the areas of the strong fluorescent phase and the weak fluorescent phase, and the formula for calculating the compatibility index is: ; In the formula, C is the compatibility index of the modified asphalt.

[0007] The higher the compatibility index value, the higher the proportion of the compatibility transition zone between the modifier and the asphalt matrix, the more fully the two-phase interface is integrated, and the better the system compatibility.

[0008] Preferably, step (2) of dividing the fluorescence image into a strong fluorescence phase, a weak fluorescence phase, and a non-fluorescent phase based on the fluorescence gray value specifically includes: setting a first threshold and a second threshold for the fluorescence gray value, wherein a gray value higher than or equal to the first threshold is a strong fluorescence phase, a gray value lower than the first threshold but higher than the second threshold is a weak fluorescence phase, and a gray value lower than or equal to the second threshold is a non-fluorescent phase.

[0009] Preferably, the first threshold value is between 110 and 130, and the second threshold value is between 80 and 100. More preferably, the first threshold is 120, and the second threshold is 90.

[0010] The first and second thresholds of this invention were determined by performing grayscale histogram statistical analysis on 50 sets of fluorescence images of different types of oil-based asphalt and 8 different types of modifiers (SBS, SBR, EVA, PE, etc.).

[0011] For most modified asphalt systems commonly used in road engineering, a first threshold of 120 and a second threshold of 90 can achieve accurate three-phase segmentation. For conventional special systems with relatively small overall fluorescence intensity shifts (such as No. 70 road petroleum asphalt from different oil sources, and ordinary linear / star-shaped SBS), the absolute value of the fixed threshold can be fine-tuned within ±10. After fine-tuning, at least three parallel images should be used to verify the accuracy of phase segmentation.

[0012] For extremely special systems with significant overall fluorescence intensity shifts (such as high-aromatic asphalt, dark-colored modifiers, and weak-fluorescence modifiers), a relative threshold method can be used for adjustment: Using the peak gray value of the asphalt matrix phase in the gray-scale histogram as a baseline, shift upwards by 30 (the inherent gray-scale spacing between the three phases, a constant value determined based on the physical mechanism of fluorescence imaging) as the second threshold (the boundary between the non-fluorescent and weakly fluorescent phases), and then shift upwards by another 30 as the first threshold (the boundary between the weakly fluorescent and strongly fluorescent phases). The core of this relative threshold method is to maintain a constant gray-scale spacing of 30 between the three phases, effectively eliminating the influence of differences in fluorescence intensity caused by different imaging equipment, exposure parameters, and the sample itself.

[0013] This invention uses the aforementioned fluorescence image processing method to assign specific physical meanings to the fluorescent regions, and uses the area fraction of the weakly fluorescent phase as a quantitative indicator to evaluate the compatibility of the modifier and asphalt, thus realizing the transformation of compatibility from qualitative observation to quantitative evaluation.

[0014] Furthermore, this invention establishes a three-phase segmentation rule based on grayscale thresholds: regions with grayscale values ​​≥120 are strong fluorescent phases, regions with grayscale values ​​between 90 and 120 are weak fluorescent phases, and regions with grayscale values ​​≤90 are non-fluorescent phases. This threshold setting is based on the physical mechanism of fluorescence imaging and the principle of grayscale histogram feature segmentation, which can minimize phase misjudgment and ensure the repeatability and comparability of data from different batches.

[0015] This invention uses the aforementioned fluorescence image processing method to assign specific physical meanings to the fluorescent regions, and uses the area fraction of the weakly fluorescent phase as a quantitative indicator to evaluate the compatibility of the modifier and asphalt, thus realizing the transformation of compatibility from qualitative observation to quantitative evaluation.

[0016] Preferably, the acquisition of the fluorescent image of modified asphalt in step (1) further includes a preprocessing step of denoising, grayscale enhancement, threshold segmentation, feature extraction and area calculation of the fluorescent image.

[0017] Under the same technical concept, the present invention also provides a method for optimizing the modifier dosage of modified asphalt, comprising the following steps: S1. Keep the types of asphalt raw materials, modifiers, and preparation process conditions completely consistent, and prepare multiple sets of modified asphalt samples with different modifier dosages. The modifier dosage is the percentage of the mass of the modifier relative to the mass of the base asphalt. S2. Using the quantitative evaluation method for the compatibility of modified asphalt based on fluorescence image analysis, the compatibility index of multiple modified asphalt samples with different modifier dosages in S1 is obtained. S3. Based on the compatibility index of S2, establish the correspondence between the modifier dosage and the compatibility index, fit the curve of the modifier dosage and the compatibility index and determine the inflection point. The inflection point is the critical dosage of the modifier that changes from significant change to stabilization or deterioration as the dosage increases. S4. Modified asphalt was prepared based on the critical modifier dosage obtained in S3.

[0018] The above method constructs a quantitative relationship curve between "modifier dosage and compatibility index" and uses the inflection point to determine the optimal dosage, thus shifting the formulation design of modified asphalt from empirical trial and error to scientific optimization. By establishing dosage-compatibility-critical value data for different types of modifiers, a reference standard library of optimal modifier dosages can be formed to guide actual production.

[0019] Preferably, the critical dosage of the modifier is the optimal dosage under the conditions of asphalt raw material type, modifier type and preparation process in step S1. When the asphalt raw material type, modifier type and preparation process conditions change, the process returns to step S1.

[0020] The "inflection point" of the compatibility index as a function of modifier dosage, as determined by this method, is not an absolute constant that does not change with conditions. This inflection point depends on the following factors: the type of asphalt matrix (e.g., oil source, component ratio); the molecular structure of the modifier (e.g., linear / star-shaped SBS, molecular weight); the type and proportion of each additive in the composite modification system; and the preparation process parameters (shear rate, shear temperature, shear time, development temperature and time, etc.).

[0021] Therefore, for the same modifier, the inflection point of its optimal dosage may shift under different raw material batches or different process conditions. The value of this method lies in its ability to quickly and quantitatively determine the optimal modifier dosage under fixed raw material and process conditions, thus replacing the traditional trial-and-error method. When the raw materials or process change, the inflection point should be re-determined using this method.

[0022] Preferably, the asphalt raw material includes one or more of the following: No. 50 road petroleum asphalt, No. 70 road petroleum asphalt, No. 90 road petroleum asphalt, Middle Eastern oil-based asphalt, or domestic oil-based asphalt. The modifiers include one or more of styrene-butadiene-styrene block copolymers, sulfur powder, peroxides, or montmorillonite. The preparation process conditions include the following parameters: shear temperature, ranging from 140℃ to 180℃; shear rate, ranging from 3000 to 5000 rpm; shear time, ranging from 0.5 to 3 h; development temperature, ranging from 150℃ to 180℃; development time, ranging from 1 to 3 h; and sample film thickness at the time of fluorescence image acquisition, ranging from 50 to 200 μm.

[0023] Preferably, the modifiers used in the remaining conditions further include: The molecular structure of the styrene-butadiene-styrene block copolymer includes linear and / or star-shaped structures; the molecular weight is 80,000 to 300,000 g / mol. The vulcanizing agent includes one or more of sulfur powder, peroxide, zinc oxide, or stearic acid; When the vulcanizing agent is sulfur powder, the purity of the sulfur powder is ≥98% and the particle size is ≤200 mesh; when the vulcanizing agent is peroxide, the purity of the peroxide is ≥95% and the particle size is ≤150 mesh. The montmorillonite is an organically modified montmorillonite with a cation exchange capacity (CEC) of 90-120 mmol / 100g and an interlayer spacing of 1.2-3.0 nm.

[0024] Preferably, when the modifier includes multiple types, the preparation of multiple sets of modified asphalt samples with different modifier dosages in step S1 specifically involves: pre-determining the mass ratio between multiple modifiers in the modifier, and then adjusting the total modifier dosage to prepare multiple sets of modified asphalt samples with different modifier dosages.

[0025] Preferably, after step S3, the method further includes the following steps: performing macroscopic performance tests on the multiple groups of modified asphalt samples with different modifier dosages to obtain macroscopic performance test results; establishing a correlation curve between modifier dosage and macroscopic performance test results based on the modifier dosage and macroscopic performance test results of the modified asphalt samples with different modifier dosages; the macroscopic performance test results include penetration and / or softening point. Based on the correlation curve between the modifier dosage and the macroscopic performance test results, the inflection point of the curve between the modifier dosage and the compatibility index is verified, and the modifier dosage is comprehensively optimized.

[0026] When the correlation curve between the modifier dosage and the macroscopic performance test results and the curve numbering pattern between the modifier dosage and the compatibility index are consistent, it verifies that the inflection point of the compatibility index curve can reflect the correlation between the microstructure and the macroscopic performance.

[0027] This invention further verifies the effectiveness of this quantitative index by analyzing the correlation between the compatibility index and the macroscopic road performance of modified asphalt. Specifically, the compatibility index of modified asphalt samples with different admixtures was compared and analyzed with the macroscopic performance test results such as penetration and softening point, and a correlation curve between the compatibility index and macroscopic performance was established. The results show that the compatibility index is significantly negatively correlated with the softening point and significantly positively correlated with the penetration, confirming that this compatibility index can effectively reflect the intrinsic relationship between the microstructure and macroscopic mechanical properties of modified asphalt.

[0028] The above-described solution of the present invention has the following beneficial effects: (1) This invention proposes for the first time to use the area fraction of weak fluorescent phase as a quantitative evaluation index of the compatibility of modified asphalt, giving clear physical meaning to different phase regions in the fluorescence image, realizing the transformation of the compatibility of modifier-asphalt from "qualitative observation" to "quantitative evaluation", effectively reducing the human error caused by relying on experience judgment in traditional evaluation methods.

[0029] (2) By constructing the relationship curve of “modifier dosage - compatibility index” and determining the inflection point, this invention can quickly and accurately determine the optimal amount of modifier to be added, providing a scientific basis for the design of modified asphalt formulations.

[0030] (3) This invention establishes a predictive model between microstructure and macro properties by verifying the correlation between compatibility index and macro properties such as penetration and softening point, making the performance regulation of modified asphalt more precise and controllable.

[0031] (4) The method of the present invention is not only applicable to SBS modified asphalt system, but can also be extended to other composite modified systems such as crosslinking agents and montmorillonite. It has good scalability and engineering application value, and is of great significance for improving the design level of modified asphalt materials and ensuring the durability of road engineering.

[0032] The present invention will now be described in further detail with reference to specific embodiments. Attached Figure Description

[0033] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1 The image shows the fluorescence of 3% SBS modified bitumen in Example 1.

[0035] Figure 2The curves showing the relationship between the area fraction of the compatible phase and the amount of modifier in the fluorescence images of different SBS modified asphalt dosages in Example 1 are shown.

[0036] Figure 3 The image shows the fluorescence of the 3% SBS + 0.15% sulfur powder composite modified asphalt in Example 2.

[0037] Figure 4 The curves showing the relationship between the area fraction of the compatible phase and the amount of modifier in the fluorescence images of different SBS+sulfur powder composite modified asphalt in Example 2 are shown.

[0038] Figure 5 The image shows the fluorescence of the 5% SBS + 0.3% OMMT composite modified bitumen in Example 3.

[0039] Figure 6 The curves showing the relationship between the area fraction of the compatible phase and the amount of modifier in the fluorescence images of different SBS+OMMT composite modified asphalt in Example 3 are shown.

[0040] Figure 7 The curves show the penetration of modified asphalt in Example 1 (pure SBS system), Example 2 (SBS + sulfur powder composite system), and Example 3 (SBS + OMMT composite system) as a function of SBS content.

[0041] Figure 8 The softening point of the modified asphalt in Example 1 (pure SBS system), Example 2 (SBS + sulfur powder composite system), and Example 3 (SBS + OMMT composite system) varies with the SBS content.

[0042] Figure 9 The curve showing the relationship between the compatibility area and its penetration / softening point in Example 1 is shown.

[0043] Figure 10 The curve showing the relationship between the compatibility area and its penetration / softening point in Example 2 is shown.

[0044] Figure 11 The curve showing the relationship between the compatibility area and its penetration / softening point in Example 3 is shown.

[0045] Figure 12 This is a technical roadmap for the quantitative evaluation method of modified asphalt compatibility and the optimization method of modifier dosage based on fluorescence image analysis of the present invention. Detailed Implementation

[0046] To make the technical problems, solutions, and advantages of this invention clearer, a detailed description will be provided below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0047] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0048] Example 1: Compatibility determination of modified asphalt with different SBS modifier dosages The technical roadmap of the embodiment is as follows: Figure 12 As shown, it includes the following steps: 1. Sample preparation Using a 0.5% mass fraction of the modifier relative to the base asphalt as a gradient, several groups of modified asphalt samples with different SBS modifier (i.e., styrene-butadiene-styrene triblock copolymer) content (hereinafter referred to as SBS content) ranging from 2.5% to 10% were prepared. The specific SBS content groupings are shown in Table 1. The specific method was as follows: the base asphalt (Grade A No. 70 road petroleum asphalt) was heated to a fluid state in an oven at 160℃, and the SBS modifier (linear molecular structure, trade number YH-791, molecular weight of 90,000 to 110,000 g / mol) was added at a shear temperature of 170~180℃. The mixture was sheared at a shear rate of 5000 rpm for 2 hours using a high-speed shear machine, and then transferred to a high-speed disperser for dispersion and development at a development temperature of 160~170℃ and a dispersion rate of 500 rpm for 2 hours to obtain the SBS modified asphalt samples.

[0049] 2. Fluorescence Image Acquisition and Compatibility Calculation A small amount of each sample was heated and leveled to prepare thin film samples of uniform thickness, with the thickness ranging from 100 μm. Images were acquired using a fluorescence microscope at 10× magnification, exposure time of 100-500 ms, and excitation wavelength of 420-490 nm. Figure 1 As shown. After denoising and grayscale enhancement, the image is segmented according to the following thresholds: grayscale value ≥120 is the strong fluorescent phase (modifier phase), 90~120 (excluding endpoints) is the weak fluorescent phase (compatible phase), and ≤90 is the non-fluorescent phase (asphalt phase).

[0050] According to the formula for calculating the compatibility index: ; The strong fluorescence phase corresponds to the modifier-enriched phase, and its area is denoted as A. The weak fluorescence phase corresponds to the modifier-asphalt compatible transition phase, and its area is denoted as B. The proportion of the weak fluorescence phase area to the total fluorescence area (strong fluorescence phase + weak fluorescence phase) is calculated to obtain the compatibility index C (%).

[0051] 2.1 Image analysis data at typical doping levels (taking 3.0% SBS doping as an example) Three fluorescence images with SBS doping of 3.0% from different fields of view were analyzed, and the specific data of the area of ​​each phase relative to the total image area are as follows: Image 1 (corresponding to this application) Figure 1 The area ratio of the strongly fluorescent phase was 17.8%, the area ratio of the weakly fluorescent phase was 59.2%, and the area ratio of the non-fluorescent phase was 23.0%. Image 2: Area ratio of strong fluorescent phase 18.5%, area ratio of weak fluorescent phase 58.5%, area ratio of no fluorescent phase 23.0%; Image 3: Area ratio of strong fluorescent phase 18.3%, area ratio of weak fluorescent phase 58.7%, area ratio of no fluorescent phase 23.0%; Calculate the average area percentage of each phase: Average area ratio of strongly fluorescent phase: (17.8% + 18.5% + 18.3%) / 3 ≈ 18.2%; Average area ratio of weakly fluorescent phase: (59.2% + 58.5% + 58.7%) / 3 ≈ 58.8%; Average area ratio of non-fluorescent phase: 23.0% (consistent across three images).

[0052] The compatibility index is calculated using the formula: C(%) = weak fluorescent phase area / (strong fluorescent phase area + weak fluorescent phase area) × 100% = 58.8 / (18.2 + 58.8) × 100% = 76.41%, which is consistent with the value corresponding to the 3.0% doping in Table 1.

[0053] 2.2 The compatibility index, softening point, and penetration of different SBS doping levels are summarized in Table 1: Macroscopic performance tests were conducted on modified asphalt samples with different SBS content. The softening point was determined according to GB / T 4507-2014 "Asphalt Softening Point Determination Method - Ring and Ball Method", and the penetration was determined according to GB / T 4509-2010 "Asphalt Penetration Determination Method". Table 1. Compatibility index, softening point, and penetration of SBS-modified asphalt at different dosages in Example 1. ; 3. Results Analysis Based on the results in Table 1, the relationship between the modifier dosage and the compatibility index was established, and the fitted curve is shown in the figure. Figure 2As shown, a fitting curve between the modifier dosage and the penetration and softening point was established based on the penetration and softening point data.

[0054] Figure 7 The penetration curves of modified asphalt in Example 1 (pure SBS system), Example 2 (SBS + sulfur powder composite system), and Example 3 (SBS + OMMT composite system) are shown as a function of SBS content. Figure 8 The softening point of the modified asphalt in Example 1 (pure SBS system), Example 2 (SBS + sulfur powder composite system), and Example 3 (SBS + OMMT composite system) varies with the SBS content. Figure 9 The curve showing the relationship between the compatibility area and its penetration / softening point in Example 1 is shown.

[0055] From Table 1 above and Figure 2 It is evident that the compatibility index initially increases and then decreases with increasing SBS content: when the SBS content increases from 2.5% to 3.0%, the compatibility index rises from 66.3% to 76.4%; however, after the content exceeds 3.0%, the compatibility index decreases significantly (from 3.5% to 65.3%, and from 4.0% to 48.5%). Based on the definition of the inflection point in this application (the critical content at which the compatibility index changes from a significant increase to a decrease with increasing content), the SBS content of 3.0% is the inflection point in this system; therefore, the optimal SBS addition is determined to be 3.0%.

[0056] As supplementary verification, the softening point continuously increases with increasing SBS doping content, while the penetration gradually decreases, showing an inherent consistency with the change pattern of the compatibility index. This indicates that the compatibility index can effectively reflect the correlation between microstructure and macroscopic properties. Furthermore, the softening point and penetration test results show that with increasing SBS doping content, the softening point increases while the penetration decreases, exhibiting an inherent consistency with the change pattern of the compatibility index.

[0057] Example 2: SBS modified asphalt with added sulfur powder 1. Sample Preparation Based on Example 1, sulfur powder (99.5% purity, 200 mesh particle size, vulcanizing agent) with a mass fraction of 0.15% relative to the mass percentage of the base asphalt was added to multiple groups of modified asphalt samples with different SBS content to prepare SBS+sulfur powder composite modified asphalt with different content. The preparation sequence was as follows: the rest of the process was the same as in Example 1, the only difference being that when adding the modifier, the SBS modifier was added first and sheared for 0.5 h at a shear temperature of 170~180℃, and then the sulfur powder was added and sheared for another 1.5 h.

[0058] 2. Image Processing and Testing The fluorescence image processing and compatibility calculation methods, as well as the testing methods for softening point and penetration, are the same as in Example 1. The fluorescence image is as follows: Figure 3 As shown.

[0059] Table 2 shows the compatibility index, softening point, and penetration of SBS+sulfur powder composite modified asphalt with different dosages.

[0060] Table 2. Compatibility index, softening point, and penetration of SBS+sulfur powder composite modified asphalt at different dosages in Example 2. ; 3. Results Analysis Based on the compatibility index results of SBS+sulfur powder composite modified asphalt with different dosages in Example 2, a fitting curve was established, as follows: Figure 4 As shown, in the presence of sulfur powder, the compatibility index gradually decreases with increasing SBS content (approximately 93% at 3% and approximately 49% at 7%), with no obvious peak value.

[0061] Figure 10 The curve showing the relationship between the compatibility area and its penetration / softening point in Example 2 is shown. Considering both compatibility and high-temperature performance, an SBS doping level in the range of 4% to 5% is more suitable.

[0062] Example 3: SBS modified asphalt with added montmorillonite 1. Sample preparation Based on Example 1, organic montmorillonite (organically modified nano-montmorillonite OMMT, cation exchange capacity CEC = 100 mmol / 100g, interlayer spacing 2.3 nm) was added to multiple groups of modified asphalt samples with different SBS contents, at a mass fraction relative to the base asphalt mass percentage, to prepare SBS+OMMT composite modified asphalt with different contents. The preparation sequence was as follows: the rest of the process was the same as in Example 1, the only difference being that when adding the modifier, montmorillonite was added first and sheared for 0.5 h at a shear temperature of 170~180℃, and then SBS was added and sheared for another 1.5 h.

[0063] 2. Image Processing and Testing The fluorescence image processing and compatibility calculation methods, as well as the testing methods for softening point and penetration, are the same as in Example 1. The fluorescence image is as follows: Figure 5 As shown.

[0064] Table 3 shows the compatibility index, softening point, and penetration of SBS+OMMT composite modified asphalt at different dosages.

[0065] Table 3. Compatibility index, softening point, and penetration of SBS+OMMT composite modified asphalt at different dosages in Example 3. ; 3. Results Analysis Based on the compatibility index results of SBS+OMMT composite modified asphalt with different admixture amounts in Example 3, a fitting curve was established, as follows: Figure 6 As shown, the compatibility index first increases and then decreases with increasing SBS doping content, reaching a peak at 5% doping (approximately 49%).

[0066] Figure 11 The curve showing the relationship between the compatibility area and its penetration / softening point in Example 3 is shown. Considering compatibility, softening point, and penetration, an SBS doping level of 4.5% to 5.5% is recommended.

[0067] summary In summary, through the comparative analysis of the three embodiments described above, the following conclusions can be drawn: (1) The compatibility index (the proportion of weak fluorescent phase area to total fluorescent area) proposed in this invention can effectively quantify the compatibility between modifier and asphalt matrix, realize the transformation of compatibility evaluation from qualitative description to quantitative characterization, and has good repeatability.

[0068] (2) The compatibility index changes non-linearly with the amount of modifier. By fitting the amount-compatibility curve and determining the inflection point, the optimal amount of modifier added for different modification systems (pure SBS, sulfur powder crosslinking, montmorillonite composite, etc.) can be quickly determined.

[0069] (3) The compatibility index is significantly correlated with the macroscopic road performance (softening point, penetration) of modified asphalt. It is negatively correlated with the softening point and positively correlated with the penetration, which confirms the intrinsic relationship between microstructure and macroscopic performance.

[0070] (4) This method is not only applicable to SBS modified asphalt systems, but can also be extended to composite modified systems containing crosslinking agents, montmorillonite and other additives, providing a scientific and efficient quantitative tool for the formulation design, performance prediction and quality control of modified asphalt.

Claims

1. A quantitative evaluation method for the compatibility of modified asphalt based on fluorescence image analysis, characterized in that, Includes the following steps: (1) Obtain fluorescence images of modified bitumen; (2) Set a first threshold and a second threshold for fluorescence gray value. A gray value higher than or equal to the first threshold is a strong fluorescent phase, a gray value lower than the first threshold but higher than the second threshold is a weak fluorescent phase, and a gray value lower than or equal to the second threshold is a non-fluorescent phase. The first threshold is between 110 and 130, and the second threshold is between 80 and 100. The strong fluorescent phase corresponds to the modifier-enriched phase, and its area is denoted as A. The weak fluorescent phase corresponds to the modifier-asphalt compatible transition phase, and its area is denoted as B. (3) Calculate the ratio of the area of ​​the weak fluorescent phase to the total fluorescent area, and use this ratio as the compatibility index of the modified asphalt; the total fluorescent area is the sum of the areas of the strong fluorescent phase and the weak fluorescent phase, and the formula for calculating the compatibility index is: ; In the formula, C is the compatibility index of the modified asphalt; Based on the aforementioned quantitative evaluation method for the compatibility of modified asphalt, a method for optimizing the dosage of modifiers in modified asphalt is designed, including the following steps: S1. Maintaining complete consistency in the types of asphalt raw materials, modifiers, and preparation process conditions, prepare multiple sets of modified asphalt samples with different modifier dosages. The modifier dosage is the percentage of the modifier mass relative to the base asphalt mass. The asphalt raw material types include one or more of No. 50 road petroleum asphalt, No. 70 road petroleum asphalt, No. 90 road petroleum asphalt, Middle Eastern oil-based asphalt, or domestic oil-based asphalt. The modifiers include one or more of styrene-butadiene-styrene block copolymers, vulcanizing agents, crosslinking aids, or montmorillonite; The molecular structure of the styrene-butadiene-styrene block copolymer includes linear and / or star-shaped structures; the molecular weight is 80,000 to 300,000 g / mol. The vulcanizing agent includes one or more of sulfur powder, peroxide, zinc oxide, or stearic acid; When the vulcanizing agent is sulfur powder, the purity of the sulfur powder is ≥98% and the particle size is ≤200 mesh; when the vulcanizing agent is peroxide, the purity of the peroxide is ≥95% and the particle size is ≤150 mesh. The montmorillonite is an organically modified montmorillonite with a cation exchange capacity (CEC) of 90-120 mmol / 100g and an interlayer spacing of 1.2-3.0 nm. The preparation process conditions include the following parameters: shear temperature, ranging from 140℃ to 180℃; shear rate, ranging from 3000 to 5000 rpm; shear time, ranging from 0.5 to 3 h; development temperature, ranging from 150℃ to 180℃; development time, ranging from 1 to 3 h; and sample film thickness at the time of fluorescence image acquisition, ranging from 50 to 200 μm. S2. Using the quantitative evaluation method for the compatibility of modified asphalt based on fluorescence image analysis, the compatibility index of multiple modified asphalt samples with different modifier dosages in S1 is obtained. S3. Based on the compatibility index of S2, establish the correspondence between the modifier dosage and the compatibility index, fit the curve of the modifier dosage and the compatibility index and determine the inflection point. The inflection point is the critical dosage of the modifier that changes from significant change to stabilization or deterioration as the dosage increases. S4. Modified asphalt was prepared based on the critical modifier dosage obtained in S3.

2. The method for quantitative evaluation of the compatibility of modified asphalt based on fluorescence image analysis as described in claim 1, characterized in that, The acquisition of the fluorescence image of modified asphalt in step (1) further includes: preprocessing steps such as denoising, grayscale enhancement, threshold segmentation, feature extraction and area calculation of the acquired fluorescence image of modified asphalt.

3. The method for optimizing the modifier dosage of modified asphalt as described in claim 1, characterized in that, The critical dosage of the modifier is the optimal dosage under the conditions of asphalt raw material type, modifier type and preparation process in step S1. When the asphalt raw material type, modifier type and preparation process conditions change, the process returns to step S1.

4. The method for optimizing the modifier dosage of modified asphalt as described in claim 1, characterized in that, When the modifiers include multiple types, the preparation of multiple sets of modified asphalt samples with different modifier dosages in step S1 specifically involves: pre-determining the mass ratio between multiple modifiers in the modifiers, and then adjusting the total dosage of the modifiers to prepare multiple sets of modified asphalt samples with different modifier dosages.

5. The method for optimizing the modifier dosage of modified asphalt as described in claim 1, characterized in that, Following step S3, the method further includes the following steps: performing macroscopic performance tests on the multiple groups of modified asphalt samples with different modifier dosages to obtain macroscopic performance test results; establishing a correlation curve between modifier dosage and macroscopic performance test results based on the modifier dosage and macroscopic performance test results of the modified asphalt samples with different modifier dosages; the macroscopic performance test results include penetration and / or softening point. Based on the correlation curve between the modifier dosage and the macroscopic performance test results, the inflection point of the curve between the modifier dosage and the compatibility index is verified, and the modifier dosage is comprehensively optimized.